PENGARUH KEPUASAN KERJA DAN KOMITMEN KARYAWAN TERHADAP KEINGINAN KARYAWAN UNTUK BERHENTI PADA PT. MAYAPADA AUTO SEMPURNA (DEALER RESMI FORD) PEKANBARU - Fifi Yanda Putri; Machasin -; Errin Yani Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research held in PT. Mayapada Auto Sempurna Pekanbaru. This research held in order to analyze the influence of job satisfaction and employee’s commitment to turnover intention. Population are all employees, consist of 57 people. Considering the number limitation so sampling method used is census that covers all employee as the respondents. Variables used are job satisfaction and employee’s commitment as independent dan turnover intention as dependent. Data analyzed by using descriptive analysis and multiple regression analysis by using SPSS 19 for windows. Result of this study shows that both job satisfaction and employee’s commitment negatively and significantly influence, either in simultenously or partially, to turnover intention. job satisfaction is the dominant factor that influence turnover intention compared to influence given by commitment factor. It is recommended to evaluate and remanage all aspect of satisfaction and strengthen employee’s commitment in order to decrease the turnover intention.Keywords: Job Satisfaction, Commitment and Turnover Intention